Caracterización de cartera de clientes HQ como herramienta para determinar su comportamiento (2018)
This paper examines and analyzes the administrative actions executed at the Accounts receivables department in Tp vision. which is a branch office of Phillips in Europe. This investigation intends to identify if the resources applied at the receivables process in the headquarters portfolio (HQ) is efficient accordingly with the evaluation of its actual management models and thus determining through financial indicators whether the management complies with their goals or not. Furthermore this study evaluates HQ portfolio behavior regarding every segment it holds whereas characterizing it in order to understand its tendencies and current situation. The type of investigation that took place throughout this research is qualitative with a descriptive and explanatory scope because its main intention is to give specific detail to the receivables process which is matter that must be completed through observation. Conclusive results put in evidence management’s efforts to preserve a healthy portfolio with the help of graphical and numerical tools.